The joint effect of asbestos exposure, tobacco smoking and alcohol drinking on laryngeal cancer risk: evidence from the French population-based case–control study, ICARE. Issue 1 (24th September 2015) - Menvielle, Gwenn; Fayossé, Aurore; Radoï, Loredana; Guida, Florence; Sanchez, Marie; Carton, Matthieu; Cyr, Diane; Schmaus, Annie; Cénée, Sylvie; Fevotte, Joëlle; Delafosse, Patricia; Stücker, Isabelle; et al.
Abstract : Objective: The objective of the study was to investigate the joint effect of occupational exposure to asbestos, and tobacco and alcohol consumption, on the risk of laryngeal cancer among men. Methods: We used data from a large population-based case–control study conducted in France. We estimated two-way and three-way interactions between asbestos exposure (never vs ever exposed), tobacco consumption (<20 vs ≥20 pack-years) and alcohol consumption (<5 vs ≥5 drinks per day). The interaction on an additive scale was assessed by estimating the relative excess risk due to interaction (RERI) and the attributable proportion due to interaction, and the interaction on a multiplicative scale was assessed by estimating the multiplicative interaction parameter (ψ). Multiplicative interactions were also assessed using fractional polynomials for alcohol drinking, tobacco smoking and asbestos exposure. Results: When compared with light-to-moderate smokers and drinkers never exposed to asbestos, the increase in laryngeal cancer risk was smallest among light-to-moderate drinkers and smokers exposed to asbestos (OR=2.23 (1.08 to 4.60)), and highest among heavy smokers and drinkers ever exposed to asbestos (OR=69.39 (35.54 to 135.5)). We found an additive joint effect between asbestos exposure and alcohol consumption (RERI=4.75 (−4.29 to 11.12)), whereas we observed a more than additive joint effect between asbestos exposure and tobacco consumption (RERI=8.50 (0.71 to 23.81)), as well as between asbestos exposure, and tobacco and alcohol consumption (RERI=26.57 (11.52 to 67.88)). However, our results did not suggest any interaction on a multiplicative scale. Conclusions: Our results suggest that asbestos exposure, in combination with tobacco and alcohol exposure, accounted for a substantial number of laryngeal cancer cases. Our findings therefore highlight the need for prevention in activities, such as construction work, where exposure to asbestos-containing materials remains.